2000
DOI: 10.1074/jbc.275.13.9805
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Signal-regulating Kinase 1 (ASK1) Induces Neuronal Differentiation and Survival of PC12 Cells

Abstract: Apoptosis signal-regulating kinase 1 (ASK1) is a ubiquitously expressed mitogen-activated protein kinase kinase kinase that activates the c-Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinase signaling cascades. We report here that expression of constitutively active ASK1 (ASK1⌬N) induces neurite outgrowth in the rat pheochromocytoma cell line PC12. We found that p38 and to a lesser extent JNK, but not ERK, were activated by the expression of ASK1⌬N in PC12 cells. ASK1⌬N-induced neurite outgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
109
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(114 citation statements)
references
References 49 publications
5
109
0
Order By: Relevance
“…This genetic evidence suggests that ASK1 may play a pivotal role in innate immune responses. Together with the findings that ASK1 induces neuronal differentiation and survival of PC12 cells and keratinocyte differentiation (Sayama et al, 2000;Takeda et al, 2000), ASK1 appears to mediate a broad range of biological activities as a determinant of cell fate.…”
Section: Emerging Roles Of Ask1 Beyond the Pro-apoptotic Signaling Inmentioning
confidence: 99%
See 1 more Smart Citation
“…This genetic evidence suggests that ASK1 may play a pivotal role in innate immune responses. Together with the findings that ASK1 induces neuronal differentiation and survival of PC12 cells and keratinocyte differentiation (Sayama et al, 2000;Takeda et al, 2000), ASK1 appears to mediate a broad range of biological activities as a determinant of cell fate.…”
Section: Emerging Roles Of Ask1 Beyond the Pro-apoptotic Signaling Inmentioning
confidence: 99%
“…Overexpression of wild-type or constitutively active ASK1 induces apoptosis in various cells through mitochondria-dependent caspase activation Kanamoto et al, 2000;Hatai et al, 2000), and ASK1 is required for apoptosis induced by oxidative stress, TNF and endoplasmic reticulum (ER) stress Nishitoh et al, 2002). On the other hand, several lines of evidence have suggested that ASK1 has diverse functions in the decision of cell fate such as differentiation and survival (Sayama et al, 2000;Takeda et al, 2000;Sagasti et al, 2001;Kim et al, 2002). Thus, ASK1 appears to be a pivotal component not only in stressinduced cell death but also in a broad range of biological activities.…”
mentioning
confidence: 99%
“…23,24 In vitro data suggest that activation of ASK1 triggers various biological responses, such as apoptosis, inflammation, differentiation, and survival in different cell types. [25][26][27][28] Studies from ASK1-deficient mice indicate that ASK1 is critical for TNF-and ROS-induced apoptosis signaling. 29 The mechanism by which stress stimuli activate ASK1 is not fully understood.…”
mentioning
confidence: 99%
“…The mitogen-activated protein kinase kinase kinase apoptosis signal-regulated kinase-1 (Ask1) and its downstream stress-activated kinases p38 and Jun NH 2 -terminal kinase (JNK) constitute an important mammalian signaling pathway that can promote cell survival, apoptosis, proliferation, or differentiation, depending on the cell type and/or cellular context (Takeda et al, 2000;Sayama et al, 2001;Sumbayev and Yasinska, 2005). Ask1 can be activated by H 2 O 2 ; thus, it is part of a redox-signaling pathway (Gotoh and Cooper, 1998;Tobiume et al, 2001;Kadowaki et al, 2005;Noguchi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In bacteria, OxyR is an archetypical H 2 O 2 sensor at the top of a redox-sensitive pathway, being activated by H 2 O 2 through formation of an intramolecular disulfide bond and controlling the transcription of antioxidant defense genes (Storz and Tartaglia, 1992;Zheng et al, 1998). In yeast, H 2 O 2 sensing involves the thiol-based peroxidase Orp1/Gpx3, which, upon oxidation by H 2 O 2 , mediates the formation of an intramolecular disulfide bond in the Yap1 transcription factor, causing its activation (Lee et al, 1999;Delaunay et al, 2002).The mitogen-activated protein kinase kinase kinase apoptosis signal-regulated kinase-1 (Ask1) and its downstream stress-activated kinases p38 and Jun NH 2 -terminal kinase (JNK) constitute an important mammalian signaling pathway that can promote cell survival, apoptosis, proliferation, or differentiation, depending on the cell type and/or cellular context (Takeda et al, 2000;Sayama et al, 2001;Sumbayev and Yasinska, 2005). Ask1 can be activated by H 2 O 2 ; thus, it is part of a redox-signaling pathway (Gotoh and Cooper, 1998;Tobiume et al, 2001;Kadowaki et al, 2005;Noguchi et al, 2005).…”
mentioning
confidence: 99%